Design of composite tank covers. (15th December 2015) - Bondyra, Agnieszka; Klasztorny, Marian; Muc, Aleksander
Abstract: The problem of design and failure analysis of composite tank covers is discussed in the paper. Covering systems consist of segmental parts of tanks, independently on tank structure. Composite covers have several advantages connected with structure, transport and assembly. Additionally, the construction divided into several sections enables repair and inspection improving. However, on the one hand, failure of the tank covers, which are occurred sometimes, and on the other hand new applications, make it necessary to develop design, analysis and optimization of these structures. In this study, the main advantages of the GRP covers are shown against other covers and roofs systems. The construction of the representative rectangular composite tank cover, segments and joints are described. Failure analysis of the covering segment under combined loading is presented. The exemplary cover was built in the sewage treatment plant in Poland. The cover is built of repetitive two-wave segments with flanges overlapping one another. The segments are made of mixed glass-fiber reinforced plastic laminates. The cover is subjected to the following static loads: dead load, technological vacuum, snow and ice and local load (workers with tools). Static analysis of the exemplary cover was conducted using the finite element code MSC.Marc. The considerations include shell geometry of the cover, structural GRP laminates with specified ply sequences, segment connections of rivet nut–bolt and anchor–nut types, friction at the interface between flanges and between flanges and tank walls. Safety coefficients have been analyzed for the different elements of the exemplary composite cover.